All about me! [large type] : my remarkable life in show business - Brooks, Mel, 1926- (Random House Large Print, 2021)
The legendary comedian, actor, and film producer and director traces his rise from a Depression-era kid in Brooklyn to his stellar film career, offering insight into the inspiration for his ideas and the many close friendships and collaborations behind his success.